Impact of Giving Remissions for the Corruptors in Indonesia - Priandina Rizki Rahayu, Achmad Irwan Hamzani, Kus Rizkianto, Nur Rohim Yunus (International Journal of Advanced Science and Technology, 2020)
The impact of remission on corruptors is not good for eradicating corruption in Indonesia. As an outside criminal, corruptors cannot be given remission. Remission will not give a deterrent effect. The purpose of this study is to examine the purpose of giving remission to prisoners of corruption and to identify the impact sociologically. This research uses a sociological approach, uses primary data, and qualitative analysis. The results showed the purpose of giving remission to corruptors to motivate in improving positive attitudes and mindsets or building and regretting their actions. This is the aim of remission in general. Another goal is for corruptors to expose larger corruption cases. However, the impact of remission does not affect the prevention of corruption. Corruption cases increase every year in volume, quantity, and quality. However, remission can reduce the overcapacity of Corrections Institutions. The provision of remission for corruptors tends to focus only on showing a good attitude to get remission. Kourpsi as an extraordinary crime should not be given remission. Corruptors must be convicted in the broadest ordinary manner as they did. It can be through impoverishment, social work, a crime that can be embarrassing so people are afraid to commit corruption.